2018
DOI: 10.1186/s12889-018-5258-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and successes in the implementation of option B+ to prevent mother-to-child transmission of HIV in southern Swaziland

Abstract: BackgroundUniversal antiretroviral therapy (ART) for all pregnant/ breastfeeding women living with Human Immunodeficiency Virus (HIV), known as Prevention of mother-to child transmission of HIV (PMTCT) Option B+ (PMTCTB+), is being scaled up in most countries in Sub-Saharan Africa. In the transition to PMTCTB+, many countries face challenges with proper implementation of the HIV care cascade. We aimed to describe the feasibility of a PMTCTB+ approach in the public health sector in Swaziland.MethodsLifelong ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…The time period-2 was associated with higher ART initiation in both interventions. Associations of temporal trends with patient outcomes have been reported previously from sub-Saharan Africa [39][40][41][42][43][44][45][46]. First, in our setting, expanding treatment eligibility increased the pool of treatment eligible patients, likely resulting in increasing ART initiations under SOC.…”
Section: Findings In Contextmentioning
confidence: 53%
“…The time period-2 was associated with higher ART initiation in both interventions. Associations of temporal trends with patient outcomes have been reported previously from sub-Saharan Africa [39][40][41][42][43][44][45][46]. First, in our setting, expanding treatment eligibility increased the pool of treatment eligible patients, likely resulting in increasing ART initiations under SOC.…”
Section: Findings In Contextmentioning
confidence: 53%
“…2010 WHO treatment eligibility recommendations) and pilot interventions for treatment expansion were introduced before becoming WHO policy (e.g. phase‐in of PMTCT option B+ and treat‐all). This allowed an increasing number of PLHIV to start treatment before presenting with advanced HIV disease, possibly resulting in a less sick and clinically more easy to manage treatment cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, from 2011 to 2012, HIV services were consolidated, and community‐based HIV testing and routine viral load monitoring were introduced (period‐3). Then, in 2013 and 2014 (period‐4), ART eligibility was further extended in Nhlangano health cluster by phasing in the prevention of mother‐to‐child transmission (PMTCT) option B+ approach in 01/2013 and universal ART provision irrespective of immunological criteria (treat‐all) in 10/2014. All services were provided free of charge by the Ministry of Health and Médecins Sans Frontières (MSF).…”
Section: Methodsmentioning
confidence: 99%
“…A modelling study suggested that ART programmes are needed to sustain high levels of ART adherence and good immunologic response to avert TB rebound [14]. TB rebound was not detected in this setting, with viral load suppression rates in ART patients being ≥84% [26,31]. Calendar year interacted with HIV and ART status.…”
mentioning
confidence: 95%